Evaluation of the on-/off-target DNA cleavage induced by Cas9 variants - Niklas, Selfjord (My University, 2019)
The CRISPR-Cas9 system of gene editing has future potential for therapeutic applications in humans. Exploration of novel Cas9 variants is currently expanding and improving the capabilities of genome engineering. A major obstacle to the clinical translation of Cas9 gene therapy is unintended mutations at off-target sites. The specificity of guide RNAs and Cas9 variants needs to be carefully evaluated prior to their therapeutic use. This thesis work aimed to explore on/off-target activity of Cas9 variants. In the first part, we have evaluated on/off-target profiles of two previously described guide RNAs known to be specific and promiscuous in single cells by sequencing the off-target sites in Cas9 treated mouse embryos. We have found that highly efficient editing with a specific guide can be achieved in embryos with no detectable off-targets. In addition, we have shown that highly efficient editing by a promiscuous guide can induce off-targets in embryos, and off-target profiles of individual embryos can be decidedly distinct. In the second part, we have evaluated the on/off-target activity of a novel Cas9 variant, AzCas9. We have demonstrated that AzCas9 can efficiently cleave the intended target site in mouse cells, and are currently evaluating its specificity in the mouse genome with a promiscuous guide using ‘circularization for in vitro reporting of cleavage effects by sequencing’ (CIRCLE-seq).
Keywords: CRISPR; Cas9; gene editing; cell transfection; off-target detection; CIRCLE-seq; next-generation sequencing